The influence of the German language on the iconicity of the grammatical forms of the adjective in the Kursenieki language - Kiseliūnaitė, Dalia (Baltistica, 2022)
The article examines the grammatical peculiarities of adjectives which emerged at the end of the 20th century in the New Curonian (Kursenieki) language of the responders and therefore were overlooked by earlier researchers. Based on the examples of the last generation of speakers, collected mainly from records documented in coherent language, emphasis is put on the breakdown of the grammatical system of adjectives: the loss of the iconicity of gender, number and case categories. The reduction of endings, observed by earlier authors as a phonological phenomenon, is examined here not only from a phonological but also from a morphosyntactic aspect. It was established that the increased number of cases of adjectives non-agreeing with the agreement controller is related to the predicate function of adjectives. The spread of non-iconic forms, which are not characteristic of the Baltic languages, is believed to be influenced by German grammar that was strengthened through schools with German as the language of instruction.